ANALISIS KEAKTIFAN BELAJAR SISWA MENGUNAKAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS IV SD NEGERI 101812 NAMO TUALANG - Zelya Margarena Br Barus; Indah Permadani; Rahma Adinda Sahara; Umi Kalsum; Alza Delia; Vierca Cantika Budi (STKIP Subang, 2025)
This research aims to analyze students' active learning using the Teams Games Tournament (TGT) learning model in Indonesian language subjects in class IV of SD Negeri 101812 Namo Tualang. Active learning is an important aspect that determines the success of the learning process. The research method used is a qualitative method with a descriptive approach. Data was obtained through observation, questionnaires, structured interviews and documentation. The research results show that the TGT learning model is effective in increasing student learning activity. Students become more involved in the learning process, both intellectually and emotionally, through group discussions, asking questions, and problem solving. This learning model also helps teachers create a fun and interactive learning atmosphere, so that students are more motivated to take Indonesian language lessons.